Linking workplace spirituality and employee commitment in Malaysian public service organizations - Wan Yunan, Wan Rahim; Ahmad, Aminah; Omar, Zoharah (Universiti Putra Malaysia Press, 2018)
For more than two decades, antecedents of employee commitment have been studied. However, few scholars have promoted spirituality as an antecedent of commitment, especially among public service employees, and the findings on the relative contribution of different spirituality dimensions to commitment were inconclusive. This study examined the experience of spirituality at work and its linkage with affective commitment among employees from four Malaysian public rural development organisations. Workplace spirituality was examined in terms of meaningfulness of work, sense of community and alignment of employee and organisational values. Questionnaire-based survey data from 274 employees were analysed. The findings indicated that the employees experienced a great sense of meaningfulness of work, sense of community and alignment with organisational values. The meaningfulness of work and alignment of values dimensions of spirituality significantly affected employee affective commitment to the organisations. However, the sense of community did not significantly affect commitment. Workplace spirituality dimensions explained 26.7% of the variance in affective commitment. Implications of the findings and suggestions for future research are discussed.